2023
DOI: 10.2471/blt.22.288650
|View full text |Cite
|
Sign up to set email alerts
|

Supply-chain factors and antimicrobial stewardship

Nduta Kamere,
Victoria Rutter,
Derick Munkombwe
et al.

Abstract: Efficient and secure supply chains are vital for effective health services worldwide. In low- and middle-income countries, the accessibility, affordability and availability of essential medicines, including antimicrobials, remain challenging. Ineffective supply chains often cause antimicrobial shortages, leading to inappropriate use of alternative agents and increasing the risk of antimicrobial resistance. Shortages, coupled with insecure supply chains, also encourage the infiltration of substandard and falsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The multiple comparisons of our beta regression model ( Table 3 ) showed that Iran had significantly higher (p < 0.05) AMC rates compared to any other country other than Uganda, and this confirms AMC is a major precipitator of AMR in Iran. Most Low-income, and Low and middle-income countries such as Egypt, Jordan, and Uganda, have high disease burdens and high resistance rates due to poor healthcare infrastructures, scarce economic resources, little or no legislative enforcement toward controlling antimicrobial access and use, poor education, and AMR awareness and ineffective AMR supply chain [ 23 , 27 , 71 , 88 91 ]. Uganda stands out amongst the 3 from our analysis as having significantly higher rates of AMC compared to any other country ( Table 3 ), which points out AMC as an important driver of AMR in Uganda.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multiple comparisons of our beta regression model ( Table 3 ) showed that Iran had significantly higher (p < 0.05) AMC rates compared to any other country other than Uganda, and this confirms AMC is a major precipitator of AMR in Iran. Most Low-income, and Low and middle-income countries such as Egypt, Jordan, and Uganda, have high disease burdens and high resistance rates due to poor healthcare infrastructures, scarce economic resources, little or no legislative enforcement toward controlling antimicrobial access and use, poor education, and AMR awareness and ineffective AMR supply chain [ 23 , 27 , 71 , 88 91 ]. Uganda stands out amongst the 3 from our analysis as having significantly higher rates of AMC compared to any other country ( Table 3 ), which points out AMC as an important driver of AMR in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Although, limited information exists about the actual magnitude of the antimicrobial resistance (AMR) issue in LICs and LMICs due to inadequate and unreliable AMR surveillance systems, however, consistently high AMR resistance rates have been reported in LICs and LMICs in all WHO GLASS reports over the years and several independent studies [ 20 , 28 ]. Also, the observed high consumption and high resistance could be attributed to an inefficient supply chain of antimicrobials leading to the inappropriate use of alternative drugs and escalating the risk of antimicrobial resistance [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many LMICs, access to antibiotics can be limited by inadequate health infrastructure and networks, limited budgets and high cost of medications, inadequate or fragmented supply chain, ineffective procurement schemes, and often competing health-care priorities. 22 , 25 , 26 , 27 , 28 Furthermore, these challenges can be compounded by the sometimes rigid regulatory requirements in many countries, making it harder for pharmaceutical companies and manufacturers to gain entry. 24 Countries might consider addressing these challenges of expanding access to antibiotics within the design of their national action plans on antimicrobial resistance.…”
Section: Defining Access Without Excessmentioning
confidence: 99%
“…The high burden of antibiotic resistance in low and middle-income countries (LMICs) is attributed to both high and inappropriate use of antibiotics [ 6 ]. In addition, an unstable supply of essential medicines in LMICs influences the inappropriate selection of antibiotic therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%